(untitled) (Bangladesh Journal of Animal Science, 2016)
An experiment was conducted to measure the feasibility of incorporating carrot (Dascusa carota) juice in the manufacture of dahi. Four different types of dahi were manufactured by adding 0, 5, 10, and 15 per cent carrot juice to skim milk. The prepared dahi samples were subjected to physical, chemical and microbiological analysis to evaluate their qualities. Data on physical, chemical and microbiological parameters were recorded and analyzed. It was observed that the addition of carrot juice with skim milk improved the physical qualities. Dahi with 5% carrot juice was superior to other dahi samples in respect of smell and taste, body and consistency and also for colour and texture. Chemical analysis showed that addition of carrot juice increased the total solids and acidity content but decreased the protein, fat, ash and pH content. Total bacterial count was higher in the dahi samples manufactured by incorporating carrot juice than the control. From this study, it was suggested that dahi could be successfully manufactured from skim milk by incorporating carrot juice and 5% was found better for this purpose. Bang. J. Anim. Sci. 2016. 45 (1): 36-43